A concentrating solar power system integrated photovoltaic and mid-temperature solar thermochemical processes. (15th March 2020) - Qu, Wanjun; Xing, Xueli; Cao, Yali; Liu, Taixiu; Hong, Hui; Jin, Hongguang
Highlights: A concentrating solar power system is investigated to harvest solar radiation. Co-producing photovoltaic electricity and solar syngas is an attractive distinction. Ultraviolet and infrared spectra produce solar syngas instead of low-grade waste heat. Absolute enhancement of greater than 6% is realized compared with individual systems. Presented system leads to a feasible strategy for cascading solar energy utilization. Abstract: The approach of cascading solar energy utilization provides access to reliable and ample supplies of energy and has thus attracted widespread attention. Currently, the hybridization of a concentrating solar photovoltaic process and a solar thermochemical process is a promising approach. This paper describes and investigates a concentrating solar power system to harvest solar energy. Co-producing photovoltaic electricity and solar thermal fuel is its attractive distinction. The visible spectrum is cast onto concentrating photovoltaics to generate electricity, and the ultraviolet and infrared spectra are used to drive methanol decomposition at approximately 250 °C. A spectral splitting parabolic trough concentrator is developed in which incident solar radiation is first split and then concentrated. Based on the measured optical data of concentrators, photovoltaics and reactor, the solar-to-electricity performance is evaluated in the proposed system. The results show that a satisfied solar-to-electricity efficiency of approximately 31.8% would be realized if monocrystalline silicon photovoltaics is adopted. In comparison to individual systems, the efficiency enhancements of about 15.3% and 6.3% are obtained. The solar-to-electricity efficiency can reach approximately 35.1% by adopting gallium arsenide. Meanwhile, the improved optical performance proves that the approach of first splitting and then concentrating sunlight is feasible and promising. Finally, the results are anticipated to lead to a new approach for improving full-spectrum solar energy utilization and guiding the establishment of a prototype in the near future.